Breast Reconstruction Using Laparoscopically Harvested Pedicled Omental Flap: Imaging Findings and a Case of Recurrence Among Eight Patients - Byon, Jung Hee; Lim, Soyeoun; Bae, Kyoungkyg; Bang, Minseo (Current Medical Imaging, 2025)
Background:Laparoscopically Harvested Pedicled Omental Flap (LHPOF) has become a viable option for breast reconstruction due to advancements in minimally invasive techniques, offering benefits like reduced postoperative pain and minimal scarring.Case Presentation:This study examines the imaging findings in eight patients who underwent breast reconstruction using a LHPOF. Imaging modalities, including mammography, ultrasonography, MRI, and CT, consistently showed reconstructed breasts with fat replacing glandular tissue and numerous internal vessels. One case of recurrence was detected, demonstrating the efficacy of conventional surveillance imaging studies in facilitating the detection of recurrences.Conclusion:This is the first report detailing imaging findings of breast reconstruction using an LHPOF, including a recurrence case. Understanding these imaging results is crucial for effective surveillance in breast cancer patients with omental flap reconstruction.
Keywords: Mastectomy